2013
DOI: 10.1002/j.2055-2335.2013.tb00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Compliance to an Antibiotic Prescribing Policy: Perspectives of Policymakers and Prescribers

Abstract: Background Antibiotic stewardship programs have been shown to reduce inappropriate institutional antibiotic use. There is no consensus on the strategies, e.g. formulary restrictions, that best improve appropriate use and reduce misuse of antibiotics. Aim To identify facilitators and barriers to compliance with an institutional antibiotic prescribing policy and to compare policymakers' perceptions about the facilitators and barriers that influence compliance with those held by prescribers. Method 5 antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several studies used models (6, 14.3%) or frameworks (4, 9.5%). Models or frameworks used more than once included the Cabana Framework of Barriers to Physician Guideline Adherence [ 44 , 52 , 56 ] and the Attitude Social Norm Self Efficacy model [ 43 , 53 ]. Some studies used a combination of two or more theories, models, or frameworks [ 40 , 55 , 60 ], two of which used one or both of the TPB or TDF [ 40 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies used models (6, 14.3%) or frameworks (4, 9.5%). Models or frameworks used more than once included the Cabana Framework of Barriers to Physician Guideline Adherence [ 44 , 52 , 56 ] and the Attitude Social Norm Self Efficacy model [ 43 , 53 ]. Some studies used a combination of two or more theories, models, or frameworks [ 40 , 55 , 60 ], two of which used one or both of the TPB or TDF [ 40 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies with prescribers of vancomycin have shown that poor knowledge of hospital antibiotic guidelines is a key reason for inappropriate antibiotic use . While providing vancomycin‐specific education to health professionals is likely to improve vancomycin dosing and TDM practices, there is limited evidence available to guide the design and implementation of effective education strategies.…”
Section: Introductionmentioning
confidence: 99%
“…57,671 Collectively, their active stewardship of antibiotic prescribing is acknowledged to limit overprescribing 672 and improve adherence to guidelines. [673][674][675][676] However, their oversight of surgical prophylaxis is constrained by the charting and timing of the administration of such drugs within the theatre environment. [677][678][679] There are many other ways in which patients may acquire infections while in hospital.…”
Section: Reducing Health-care-associated Infectionmentioning
confidence: 99%